The Effect of Argumentation-Supported Problem-Based Learning Method in Teaching Chemical Equilibrium and Le-Chatelier’s Principle - Hatice Güngör Seyhan; Gülseda Eyceyurt Türk (Universitas Pendidikan Indonesia, 2022)
This study aims to examine the effects of argumentation-supported problem-based learning (AS-PBL) carried out in the Chemistry-II laboratory course on the conceptual understanding of prospective science teachers about